Eristic Argumentation in Advertising - Biržietienė, Skirmantė; Gabrėnaitė, Eglė (Respectus Philologicus, 2014)
Advertising may be examined as a particular form of rhetoric the aims of which are the same as of rhetoric, namely to affect mind, will, feelings, and to persuade. The theory of rhetoric, the main object of which is discourse not only in narrow meaning (as verbal expression of ideas (i.e. to say text)), but also in broad meaning – as a communicative act between the addresser and the addressee since its interdisciplinary nature provides the right tools to explore the advertising discourse. The theory of rhetoric is successfully applied in development of advertising discourse, because it helps to foresee the communicative act between the addresser and the addressee. Advertising and rhetoric are combined by many common elements, but the same goal is the most important: both, rhetoric and advertising seek for persuasion through verbal and non-verbal measures.The paper deals with the analysis of the inventive level of advertising discourse, i.e., eristic arguments, spread of ways of proofing / persuasion. Eristic argumentation is a dominant argumentation type in advertising. This method of persuasion is a way to create truth visibility although it is just superficial. The most typical schemes of eristic argumentation used in advertising are as follows: argumentum ad vanitatem (appeal to the vanity of the addressee), argumentum ad verecundiam (appeal to the authority), argumentum baculinum (method of “whip” argument), argumentum ad novitatem (appeal to novelty). The article shows the usage of eristic arguments in Lithuanian commercial ads.
Keywords: eristic; eristic arguments; persuasion; rhetoric of advertising